Donor plasmacytoid dendritic cells modulate effector and regulatory T cell responses in mouse spontaneous liver transplant tolerance. Issue 6 (4th January 2021) - Nakano, Ryosuke; Yoshida, Osamu; Kimura, Shoko; Nakao, Toshimasa; Yokota, Shinichiro; Ono, Yoshihiro; Minervini, Marta I.; Geller, David A.; Thomson, Angus W.
Abstract: We assessed the role of donor liver non‐conventional plasmacytoid dendritic cells (pDCs) in spontaneous liver transplant tolerance in a fully MHC‐mismatched (C57BL/6 (H2 b ) to C3H (H2 k )) mouse model. Compared with spleen pDCs, liver pDCs expressed higher levels of DNAX‐activating protein of 12 kDa and its co‐receptor, triggering receptor expressed by myeloid cells 2, and higher ratios of programed death ligand‐1 (PD‐L1):costimulatory CD80/CD86 in the steady state and after Toll‐like receptor 9 ligation. Moreover, liver pDCs potently suppressed allogeneic CD4 + and CD8 + T cell proliferative responses. Survival of pDC‐depleted livers was much poorer (median survival time: 25 days) than that of either untreated donor livers or pDC‐depleted syngeneic donor livers that survived indefinitely. Numbers of forkhead box p3 (FoxP3) + regulatory T cells in grafts and mesenteric lymph nodes of mice given pDC‐depleted allogeneic livers were reduced significantly compared with those in recipients of untreated livers. Graft‐infiltrating CD8 + T cells with an exhausted phenotype (programed cell death protein 1 +, T cell immunoglobulin and mucin domain‐containing protein 3 + ) were also reduced in recipients of pDC‐depleted livers. PD1‐PD‐L1 pathway blockade reversed the reduction in exhausted T cells. These novel observations link immunoregulatory functions of liver interstitial pDCs, alloreactive T cell exhaustion, and spontaneous liver transplant tolerance. Abstract : The authors' observations link immunoregulatory functions of donor liver–derived plasmacytoid dendritic cells, expansion of host regulatory T cells, and alloreactive T cell exhaustion to spontaneous transplant tolerance.